2011
DOI: 10.1002/cbdv.201000284
|View full text |Cite
|
Sign up to set email alerts
|

Armenin and Isoarmenin – Two Prenylated Coumarins from the Aerial Parts of Artemisia armeniaca

Abstract: The reversed-phase (RP) preparative HPLC analyses of the MeOH extract of the aerial parts of Artemisia armeniaca yielded four prenylated coumarins, 7-hydroxy-8-(4-hydroxy-3-methylbutoxy)coumarin (named armenin), 8-hydroxy-7-(4-hydroxy-3-methylbutoxy)coumarin (named isoarmenin), lacarol, and deoxylacarol, together with five other compounds, including three flavonoid glycosides, quercetin 3-O-β-D-glucopyranoside, rutin, and kaempferol 3-O-β-D-glucopyranoside, and chlorogenic acid, and tryptophan. (10E,12Z)-9-Hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Only in two species, A. latifolia and A. tanacetifolia , coumarin-hemiterpene esters, such as lacarol ( 74 ), desoxylacarol ( 83 ) and methyllacarol ( 91 ) were identified. Both species are related to the Laciniatae subsection of the Abrotanum section, that contains A. laciniata and A. armeniaca , which 74 , 83 , and 91 were identified earlier (Hofer et al, 1986 ; Mojarrab et al, 2011 ). Such a limited rate of detectability of these compounds, only within the subsection Laciniatae, indicates their considerable chemosistematic significance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Only in two species, A. latifolia and A. tanacetifolia , coumarin-hemiterpene esters, such as lacarol ( 74 ), desoxylacarol ( 83 ) and methyllacarol ( 91 ) were identified. Both species are related to the Laciniatae subsection of the Abrotanum section, that contains A. laciniata and A. armeniaca , which 74 , 83 , and 91 were identified earlier (Hofer et al, 1986 ; Mojarrab et al, 2011 ). Such a limited rate of detectability of these compounds, only within the subsection Laciniatae, indicates their considerable chemosistematic significance.…”
Section: Discussionmentioning
confidence: 84%
“…Specific MS/MS patterns of 74 showed an [M+H] + ion with m / z 295, two adduct ions with m / z 317 [M+Na] + and 339 [M+HCOO] + and fragments initiate by the elimination of water { m / z 277 [(M–H 2 O)+H] + } and 4′-hydroxy-3′-methylbythoxy-group { m / z 209 [(M–C 5 H 10 O)+H] + ; 195 [(M–C 5 H 10 O–CH 2 )+H] + }. Thus, it was characterized as 5-hydroxy-7-methoxy-8-(4′-hydroxy-3′-methylbythoxy)coumarin or lacarol, previously isolated from A. laciniata (Hofer et al, 1986 ) and A. armeniaca (Mojarrab et al, 2011 ). Compound 83 is similar to 74 MS-fragmentation, with an m / z difference of 16 Da less for all general fragments, indicating a compound structure as the desoxy-analog of lacarol or 7-methoxy-8-(4′-hydroxy-3′-methylbythoxy)coumarin (desoxylacarol).…”
Section: Resultsmentioning
confidence: 99%
“…Through spectroscopic analysis, these compounds [ Figure 2c ] were identified as trehalose (1), cordycepin (2), 6-hydroxyethyladenosine (3), nicotinic amide (4), butyric acid (5), β-dimorphecolic acid (6), α-dimorphecolic acid (7), palmitic acid (8), linoleic acid (9), cordycepeptide A (10), 4-(2-hydroxy-3-((9 E ,12 E )-octadeca-9,12-dienoyloxy) propoxy)-2-(trimethylammonio) butanoate (11), 4- (2-hydroxy-3-(palmitoyloxy) propoxy)-2-(trimethylammonio) butanoate (12), and linoleic acid methyl ester (13) by comparison with their previously published spectroscopic data. [ 14 15 16 17 18 19 20 ] Of these compounds, cordycepeptide A (10), 4-(2-hydroxy-3-((9E,12E)-octadeca-9,12-dienoyloxy) propoxy)-2-(trimethylammonio) butanoate (11), and 4-(2-hydroxy-3-(palmitoyloxy) propoxy)-2-(trimethylammonio) butanoate (12) were isolated for the first time from the C. militaris , indicating that these compounds could potentially serve as useful chemotaxonomic markers for this mushroom.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found the content of 6 -O-caffeoylarbutin, which had a moderate correlation with the values of α-glucosidase and pancreatic lipase inhibitory activities (r = −0.7104 and −0.6919, respectively, p < 0.05). There are also studies that have shown that caffeic acid (3) [27], quercetin-3-O-arabinofuranoside (5) [28], and kaempferol-3-O-β-D-glucopyranoside ( 9) have a positive effect on antioxidant activity [29].…”
Section: Antioxidant Activitiesmentioning
confidence: 99%